Partition Dimension of Complete Multipartite Graph - Safriadi Safriadi; Hasmawati Hasmawati; Loeky Haryanto (Jurnal Matematika, Statistika dan Komputasi, 2020)
Determining a resolving partition of a graph is an interesting study in graph theory due to many applications like censor design, compound classification in chemistry, robotic navigation and internet network. Let  and , the distance between  an  is . For an ordered partition  of , the representation of  with respect to  is . The partition  is called a resolving partition of  if all representation of vertices are distinct. The partition dimension of graph  is the smallest integer  such that  has a resolving partition with  element.In this thesis, we determine the partition dimension of complete multipartite graph  ,  which is limited by , with  and . We found that , , and , .